PROBLEMS OF INFORMATIZATION OF MODERN HIGHER PHARMACEUTICAL EDUCATION IN UKRAINE AND MEANS OF SOLUTION - Slipchuk, V. L. (Continuing Professional Education: Theory and Practice, 2019)
The questions related to the actual today problems informatization of modern higher pharmaceutical education and the ways to solve them by means of informationallearning environment of higher education. Implementation across university pharmaceutical profile of informationallearning environment, which includes knowledge and practical experience of the faculty within each discipline and interdisciplinary communication, will change the structure of the process, creating new technology training. It is shown that the process of informatization of modern higher pharmaceutical education must have comprehensive, well constructed informationallearning environment of pharmaceutical university profile should cover all, without exception, its functional subsystems. Using software professional designation allow future pharmacists, the theoretical knowledge integrated into a system of knowledge, to form and strengthen their professional skills and knowledge through imitation of a real professional. Formation of information culture future specialist pharmacists one of the problems of informatization of education